Sprawy spadkowe w umowie polsko-ukraińskiej z 1993 r. - Pazdan, Maksymilian (Problemy Prawa Prywatnego Międzynarodowego, 2022)
The article is dedicated to the matters of succession in the Agreement of 1993 on Legal Aid concluded between Poland and Ukraine. The author touches upon a number of issues. First, he discusses the role of the “general compatibility clause” provided for in Article 97 of the 1993 Agreement. He concludes that the clause does not produce effects with regard to the Regulation (EU) No 650/2012. Under the “general compatibility clause”, in all situations where the 1993 Agreement does not provide for a rule being the equivalent of the rules laid down in the Hague Convention of 1961 determining the law applicable to the form of a testamentary disposition, in Poland, in relations between Poland and Ukraine, the law applicable to the form of a testament is to be determined pursuant to the provisions of the Hague Convention of 1961. Second, the author discusses the conflict-of-laws rules set out in the Agreement which designate, as the applicable law, either Polish or Ukrainian law. He contends that where the deceased is a Polish and Ukrainian national, in order to determine which of those nationalities have to be taken into account for the purposes of Article 37 (1) of the 1993 Agreement, the criterion of the most effective (more closely connected) nationality should be relied on. However, the situations that involve a deceased of Polish or Ukrainian nationality, who is also a third-State national, do not fall within the scope of the 1993 Agreement. The application of the 1993 Agreement is, on the other hand, not barred by the fact that an immovable property in a third State forms part of the estate. Jurisdiction and the law applicable to the succession of such immovable property must be determined, both in Poland and in Ukraine, pursuant to their general conflict-of-laws regulations on matters of succession. The author explains also that the drafters of the 1993 Agreement (in Articles 37 (1) and (2)) ruled out the principle of unity of succession in favour of the principle of scission, employing the connecting factors of nationality and of location of the immovable property. This results in numerous complications in the determination of the applicable law and in its application. However, the law applicable to succession determined on the basis of Article 37 (1) and (2) of the 1993 Agreement of 1993 governs the succession as a whole, with the exception of issues covered by other rules provided for in that agreement (for example, Article 39) and of the issues that do not fall within its scope of the 1993 Agreement. Although Article 39 (1) of the 1993 Agreement expressly mentions only consequences of defective consent, there is no doubt that the said rule also covers the legal requirements for effective declaration of consent. Third, the author addresses the function of Article 38 of the 1993 Agreement, which is a substantive law provision on the estate without a claimant. This provision enjoys priority over Article 33 of the Regulation No 650/2012. Article 38 solely determines the State (Poland or Ukraine) acquiring the estate without a claimant. The concerned State enjoys the competence to designate the entity that will become the subject of rights and obligations forming part of the estate without a claimant. Finally, the author comments on the pending case resulting from the preliminary question posed by the Opole District Court (Sąd Okręgowy, case no II Czz. 438/21). The Opole Court requested from the European Court a ruling on whether a Ukrainian national residing in Poland may, under Article 22 of the Regulation No 650/2012, choose Ukrainian law. The author suggests, that — although not without a doubt — it is tempting to answer this question in the affirmative. The argument here is that the freedom to choose the applicable law in matters of succession falls entirely outside the ambit of the 1993 Agreement and so the Agreement does not preclude the choice.